Age related changes in EMG profiles and muscle length patterns during gait in healthy growing children and adults - Desloovere, K.; Molenaers, G. (Ninth International Symposium on the 3-D Analysis of Human Movement, June 28-30, 2006, Valenciennes, France, 2006)
Lower limb EMG activity, as well as muscle length patterns were estimated for a large group of healthy growing children and adults. Variability in EMG phases and muscle length patterns (determined from the 3D kinematic data using a musculoskeletal model) were described for six age groups. Different types of EMG patterns were observed per muscle group, in all ages. In addition, significant developments with age could be recognized for a variety of EMG parameters. Differences between age groups were mainly found in stance phase. Except for the quadriceps, the duration of activity (expressed as percentage of gait cycle) decreased with increasing age. Except for the triceps, the muscle length patterns (lengthening, shortening, isometric) were mature at 3 years of age.